2017
DOI: 10.1186/s40168-017-0259-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel soil-inhabiting clades fill gaps in the fungal tree of life

Abstract: BackgroundFungi are a diverse eukaryotic group of degraders, pathogens, and symbionts, with many lineages known only from DNA sequences in soil, sediments, air, and water.ResultsWe provide rough phylogenetic placement and principal niche analysis for >40 previously unrecognized fungal groups at the order and class level from global soil samples based on combined 18S (nSSU) and 28S (nLSU) rRNA gene sequences. Especially, Rozellomycota (Cryptomycota), Zygomycota s.lat, Ascomycota, and Basidiomycota are rich in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
144
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 45 publications
(72 reference statements)
5
144
0
Order By: Relevance
“…3); Tedersoo et al. ) suggest that Rozella is sister to a highly diverse clade comprising LB‐Microsporidia, the microsporidian‐like protists described above, and a large diversity of uncharacterized environmental sequences. In this study we investigate these relationships further, integrating morphological, phylogenetic, and sequence diversity data, to determine the phylogenetic and taxonomic boundaries of microsporidia and their immediate relatives.…”
mentioning
confidence: 99%
“…3); Tedersoo et al. ) suggest that Rozella is sister to a highly diverse clade comprising LB‐Microsporidia, the microsporidian‐like protists described above, and a large diversity of uncharacterized environmental sequences. In this study we investigate these relationships further, integrating morphological, phylogenetic, and sequence diversity data, to determine the phylogenetic and taxonomic boundaries of microsporidia and their immediate relatives.…”
mentioning
confidence: 99%
“…), and Antonospora locustae (Tedersoo et al. ). Most members of this lineage derive from soil and freshwater habitats, but also from some marine habitats.…”
mentioning
confidence: 99%
“…,b; James and Berbee ; Tedersoo et al. ) or with nonfungal organisms in Holomycota (e.g. Karpov et al.…”
mentioning
confidence: 99%
“…Because microscopy-based identification is time consuming and laborious, researchers commonly choose to proceed with the molecular identification, even without collecting morphological data on the species. The molecular identification of microorganisms is performed based on the amplification of the 16S rRNA gene for bacteria, cyanobacteria, and archaea (e.g., [90][91][92]), and on the 18S and/or 28S rRNA gene for fungi (e.g., [93,94]). The sequences of these genes are used in microbial taxonomic studies for several reasons: the 16S rRNA gene is found in almost all bacteria, cyanobacteria, and archaea, often as a multigene family or within operons; its function has not changed over time, suggesting that random changes in sequences are a more accurate measure of time (evolution); and the size of this gene, approximately 1500 bp, is large enough for computing purposes [95].…”
Section: The Primary Methods Of Detection In Use Have Already Become mentioning
confidence: 99%